Geschlecht zwischen Struktur und Subjekt Theorie, Praxis, Perspektiven - Graf, Julia; Ideler, Kristin; Klinger, Sabine (Verlag Barbara Budrich, 2012)
What relevance does gender have as a structuring and structured characteristic within the present circumstances? The authors - dissatisfied with the scientific state of the art - animate this discussion and lead it into new regions of thought. The concept of structure refers to social relations and institutions and focuses on inequalities, always in relation to social and institutional (gender) relations. To this end, the concept of the subject refers to actions and thus focuses more on individuals. The essential question here is: What relevance does gender have as a structuring and structured characteristic within current social conditions, structures and norms? In addition to theoretical contributions to already established subject- and structure-theoretical considerations, other authors concentrate on research-practical turns of the theoretical concepts. This volume aims to capture a dialectical interweaving of individual and social structuring processes in relation to gender.